2021
DOI: 10.3390/cancers13102332
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Preclinical Efficacy of Lurbinectedin in Malignant Pleural Mesothelioma

Abstract: Background: Malignant pleural mesothelioma (MPM) is a highly aggressive cancer generally diagnosed at an advanced stage and characterized by a poor prognosis. The absence of alterations in druggable kinases, together with an immune-suppressive tumor microenvironment, limits the use of molecular targeted therapies, making the treatment of MPM particularly challenging. Here we investigated the in vitro susceptibility of MPM to lurbinectedin (PM01183), a marine-derived drug that recently received accelerated appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Lubrinectedin acts by binding specific DNA sites thus impeding the access of transcriptional machinery and by inhibiting the function of tumor-associated macrophages (Santamaría Nuñez et al, 2016). A preliminary in vitro study showed a high sensitivity of MMe cell lines to Lubrinectidin, regardless of the BAP1 status and histological subtype (Anobile et al, 2021). Specifically, the inhibition in tumor growth was caused by the stop of the cell cycle in the S-phase with the activation of the DNA damage response and consequent apoptotic cell death.…”
Section: Novel Cytotoxic Chemotherapy Agentsmentioning
confidence: 99%
“…Lubrinectedin acts by binding specific DNA sites thus impeding the access of transcriptional machinery and by inhibiting the function of tumor-associated macrophages (Santamaría Nuñez et al, 2016). A preliminary in vitro study showed a high sensitivity of MMe cell lines to Lubrinectidin, regardless of the BAP1 status and histological subtype (Anobile et al, 2021). Specifically, the inhibition in tumor growth was caused by the stop of the cell cycle in the S-phase with the activation of the DNA damage response and consequent apoptotic cell death.…”
Section: Novel Cytotoxic Chemotherapy Agentsmentioning
confidence: 99%
“…Lurbinectedin has significant antitumor efficacy with tolerable AEs in patients with platinum-sensitive and platinum-resistant SCLCs and in those with recurrent SCLCs after second-line treatment, and this agent has been approved by the FDA for patients with metastatic SCLCs with disease progression on or after platinum-based chemotherapy ( 23 , 24 ). Lurbinectedin has also shown activity against malignant pleural mesothelioma ( 25 , 26 ); sarcoma, especially leiomyosarcoma, myxoid liposarcoma, and dedifferentiated liposarcoma ( 22 ); and ovarian ( 27 29 ) and endometrial carcinoma ( 29 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the search for new targets, Yang et al demonstrated that the exploration of aberrant biochemical networks and potential drug vulnerabilities induced by tumor suppressor loss provide interesting prospects for the treatment of MM [ 16 ]. Moreover, Anobile, Bironzo et al evaluated the preclinical efficacy of a new marine-derived anticancer drug in patient-derived samples of MM [ 17 ]. Finally, Kotecha, Tonse et al provided baseline comparative values in their review of survival of MM patients treated with systemic therapy combinations for locally, advanced, or metastatic disease [ 18 ], and Dulloo et al reviewed new opportunities in molecular strategy therapy for this cancer [ 19 ].…”
mentioning
confidence: 99%